2024
DOI: 10.3390/plants13020148
|View full text |Cite
|
Sign up to set email alerts
|

24-Epibrassinolide Reduces Drought-Induced Oxidative Stress by Modulating the Antioxidant System and Respiration in Wheat Seedlings

Azamat Avalbaev,
Vadim Fedyaev,
Alsu Lubyanova
et al.

Abstract: Brassinosteroids (BRs) represent a group of plant signaling molecules with a steroidal skeleton that play an essential role in plant adaptation to different environmental stresses, including drought. In this work, the effect of pretreatment with 0.4 µM 24-epibrassinolide (EBR) on the oxidant/antioxidant system in 4-day-old wheat seedlings (Triticum aestivum L.) was studied under moderate drought stress simulated by 12% polyethylene glycol 6000 (PEG). It was revealed that EBR-pretreatment had a protective effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 102 publications
1
2
0
Order By: Relevance
“…Proline accumulation in droughtstressed plants has been observed many times previously [56,57]. BR treatment of plants is also known to stimulate proline accumulation under water deficit [13,15,20]. At the same time, we showed that pretreatment of barley plants with BRs followed by drought partially reduced stress-induced proline accumulation, despite the fact that in this case there was stimulation of P5CS1 gene expression of proline synthesis and inhibition of its degradation gene expression (Table 4).…”
Section: Plant Oxidative Status Under Drought and 28-homobrassinoster...supporting
confidence: 72%
See 2 more Smart Citations
“…Proline accumulation in droughtstressed plants has been observed many times previously [56,57]. BR treatment of plants is also known to stimulate proline accumulation under water deficit [13,15,20]. At the same time, we showed that pretreatment of barley plants with BRs followed by drought partially reduced stress-induced proline accumulation, despite the fact that in this case there was stimulation of P5CS1 gene expression of proline synthesis and inhibition of its degradation gene expression (Table 4).…”
Section: Plant Oxidative Status Under Drought and 28-homobrassinoster...supporting
confidence: 72%
“…Pretreatment of plants with HBL slightly (by 20%) stimulated TBARS accumulation, while HCS, on the contrary, relieved the drought-induced increase in TBARS content (Figure 3), i.e., at the level of the lipid peroxidation process, lactone-and ketone-containing BRs had opposite effects on plants under drought conditions. Pretreatment of wheat plants with 24-epibrassinolide followed by PEG6000-induced water deficit also resulted in a reduction in lipid peroxidation and electrolyte leakage from tissues [15]. Pretreatment of barley plants with HCS followed by drought increased SOD activity sevenfold, had no effect on catalase activity, and slightly decreased peroxidase activity relative to water deficit.…”
Section: Plant Oxidative Status Under Drought and 28-homobrassinoster...mentioning
confidence: 93%
See 1 more Smart Citation